Analisis Rasionalisasi Ritual Tepung Tawar Dalam Pelaksanaan Gunting Rambut Pada Masyarakat Etnis Melayu Kelurahan Batulayang Kota Pontianak - Novita, Serly; Imran, Imran; Ramadhan, Iwan; Sikwan, Agus; Ismiyani, Nining (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to determine the rationalization of the ritual of white flour in the ethnic Malay community in Batulayang Village, Pontianak City. The method used is descriptive qualitative. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The analysis in this study is presented descriptively using 4 informants. The results show that the white flour ritual in hair clippers is still carried out by the Malay ethnic community in Batulayang Village which contains rational functions and meanings but is not known by the people who actually believe that the white flour ritual is only to reject reinforcements. This is evidenced by the existence of rationalization in the process of carrying out the white flour ritual in the implementation of hair clipping into three namely albarzanji reading, fresh flour ritual and closing prayer. In addition, there is also a rationalization of the ritual function of plain flour in the implementation of hair clipping which is divided into two, namely the function as a guide for individual behavior and the function as social control. And also in the white flour ritual in the implementation of hair clipping there is a rationalization of meaning which is divided into three, namely meaning in the religious aspect, meaning in the cultural aspect and meaning in the educational aspect.